Therapeutic effects of oral administration of lytic Salmonella phages in a mouse model of non-typhoidal salmonellosis - Sukjoi, Chutikarn; Buddhasiri, Songphon; Tantibhadrasapa, Arishabhas; Kaewsakhorn, Thattawan; Phothaworn, Preeda; Nale, Janet Y.; Lopez-Garcia, Angela V.; AbuOun, Manal; Anjum, Muna F.; Malik, Danish J.; Galyov, Edouard E.; Clokie, Martha R. J.; et al. (Frontiers in Microbiology, 2022)
Acute non-typhoidal salmonellosis (NTS) caused by a Gram-negative bacterium Salmonella enterica serovar Typhimurium (S. Tm) is one of the most common bacterial foodborne diseases worldwide. Bacteriophages (phages) can specifically target and lyse their host bacteria, including the multidrug-resistant strains, without collateral damage to other bacteria in the community. However, the therapeutic use of Salmonella phages in vivo is still poorly investigated. Salmonella phages ST-W77 and SE-W109 have previously been shown by our group to be useful for biocontrol properties. Here, we tested whether phages ST-W77 and SE-W109 can reduce Salmonella invasion into cultured human cells and confer a therapeutic benefit for acute NTS in a mammalian host. Human colonocytes, T84 cells, were treated with phages ST-W77, SE-W109, and its combination for 5 minutes before S. Tm infection. Gentamicin protection assays demonstrated that ST-W77 and SE-W109 significantly reduced S. Tm invasion and inflammatory response in human colonocytes. Next, streptomycin-pretreated mice were orally infected with S. Tm (108 CFU/mouse) and treated with a single or a combination of ST-W77 and SE-W109 (1010 PFU/mouse for four days) by oral feeding. Our data showed that phage-treated mice had lower S. Tm numbers and tissue inflammation compared to the untreated mice. Our study also revealed that ST-W77 and SE-W109 persist in the mouse gut lumen, but not in systemic sites. Together, these data suggested that Salmonella phages ST-W77 and SE-W109 could be further developed as an alternative approach for treating an acute NTS in mammalian hosts.